2008
DOI: 10.1080/15275920701506193
|View full text |Cite
|
Sign up to set email alerts
|

Trace Metal Concentrations in Zooplankton from the Eastern Arabian Sea and Western Bay of Bengal

Abstract: Cd, 18.7 µg g −1 ; and Pb, 6.55 µg g −1 ) were found to be higher of comparable magnitudes than the Arabian Sea zooplankton (Fe, 1786 µg g −1 ; Co, 14.2 µg g −1 ; Ni, 18.6 µg g −1 ; Cu, 21.5 µg g −1 ; Zn, 374 µg g −1 ; Cd, 16.5 µg g −1 ; and Pb, 4.0 µg g −1 ). The spatial variability of metal contents in zooplankton from both basins indicates that it is markedly enriched in coastal samples than offshore samples. The metal enrichment in zooplankton from the coastal areas of the eastern Arabian Sea occurs due to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…Coastal zooplanktons are under direct anthropogenic influence from the coast, with heavier riverine influence than offshore waters. Offshore waters are influenced by basin‐scale physical mixing processes, including cyclonic eddies during winter monsoon in the western Bay of Bengal (Rejomon et al,2008).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Coastal zooplanktons are under direct anthropogenic influence from the coast, with heavier riverine influence than offshore waters. Offshore waters are influenced by basin‐scale physical mixing processes, including cyclonic eddies during winter monsoon in the western Bay of Bengal (Rejomon et al,2008).…”
Section: Discussionmentioning
confidence: 99%
“…To explore seasonal variations in the trace metal concentration of seawater and zooplankton in the Bay of Bengal, we compared the average metal concentration in seawater and zooplankton during summer monsoon from the Bay of Bengal (Table IX), to the reported average metal concentrations in seawater (μg L −1 ) [Fe‐2.34, Co‐0.076, Ni‐0.046, Cu‐0.895, Zn‐1.38, Cd‐0.026, and Pb‐0.306] and zooplankton (μg g −1 ) [Fe‐14073, Co‐24.2, Ni‐29.5, Cu‐46.2, Zn‐2000, Cd‐18.7, and Pb‐6.55] during winter monsoon from the Bay of Bengal (Rejomon et al,2008). The average metal concentrations in the seawater and zooplankton during the summer monsoon (present study) are considerably higher than those found during the winter monsoon.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding Zn and Cu the reported patterns are in good agreement with the literature obtained in the present study. High accumulation of Zn in zooplankton may be due to coprecipitation of Zn with calcium carbonate [34].…”
Section: Fig 1 Sampling Region рис 1 район отбора пробmentioning
confidence: 99%
“…In general, they use a metal chemical analysis approach (Fang and Yang, 2010). Some studies have included biological parameters, emphasizing the monitoring of contaminants in organisms tissues (Rejomon et al, 2008). A new approach is the geochemical condition of surface sediments, by the elemental interactions, using statistical methods and factor analysis (Balachandran et al, 2006).…”
Section: Discussionmentioning
confidence: 99%